Enhanced beta to alpha recrystallization in beta isotactic polypropylene with different thermal histories. Issue 2 (20th December 2018) - Lu, Ying; Lyu, Dong; Cavallo, Dario; Men, Yongfeng
Abstract: A small but meaningful increase in the content of β‐crystals was observed in β‐nucleated isotactic polypropylene (iPP) samples isothermally crystallized at high temperature and then cooled to room temperature. The secondary crystallization of these crystals could also be linked to a distinct exothermic effect revealed by differential scanning calorimetry upon cooling. These crystals constituted of thinner lamellae certainly show earlier melting upon reheating, with respect to the isothermally crystallized fraction. As such, the enhancement in βα recrystallization in iPP cooled below 100°C is attributed to the formation of a self‐nucleated or partially ordered melt upon melting of these crystals, which induces the fast nucleation and growth of the α‐phase, because of larger undercooling with respect to the β‐phase at elevated temperatures. On the other hand, the recrystallization of the β‐phase from partially molten β‐iPP samples is tentatively assigned to homo‐epitaxial nucleation on the surface of thicker β‐phase lamellae. Abstract : The enhancement of βα‐recrystallization in β‐iPP cooled below 100°C was proposed to be associated with thin β‐crystals generated during cooling. These crystals melted earlier and survived as local orders in the melt, providing self‐nuclei for inducing the growth of α phase during heating.